Sequence Phase Analysis of Phased Rectifier - Chen Zhong-Xiao; Li Yan-Fang; Zhang Li-Guang; Chen Xing-Yu (Institute of Advanced Engineering and Science, 2013)
At present, three-phase bridge type full controlled is the most widely applied in all kinds of rectifier circuit. To guarantee the normal work of the phase control circuit, it is the most important thing that should be according to the size of the triggering angle at the right moment to the thyristor trigger of the circuit on effective puls. Nature commutation point is the earliest time of the thyristor trigger conduction, it is the starting point of thyristor trigger calculation angle, if want to change the size of the thyristor can only be based on this increase. It is difficult that to find a natural commutation point of the rectifier circuit. Find nature commutation point can be analyzed corresponding thyristor turn-on. But generally find natural commutation point will be lag behind, lead to trigger angle lags behind, according to this problem can make anyone phase voltage delay after zero, so natural commutation point can make the output voltage to achieve maximum. In fact, the above process is to realize sequence analysis and sequence adaptive. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2460